The role of endogenous elicitor peptides in plant resistance to biotic stress - Filiptsova, Halina G. (Experimental Biology and Biotechnology, 2019)
Plant elicitor peptides (Peps) are one class of elicitor substances, which are formed in plant cells in response to various biotic stressors and induced of nonspecific plant resistance. They are present and active in angiosperms, including many important agricultural crops, and can be considered as a promising class of compounds for creating environmentally safe drugs that induce phytoimmunity and increase the resistance of plants to stress. In this paper, an analysis of current literature data on the functional activity of endogenous plant elicitor peptides, the mechanisms of Pep-signaling and their role in plant resistance to biotic stresses is carried out.